A review of the osteoderms of lizards (Reptilia: Squamata). (16th August 2021) - Williams, Catherine; Kirby, Alexander; Marghoub, Arsalan; Kéver, Loïc; Ostashevskaya‐Gohstand, Sonya; Bertazzo, Sergio; Moazen, Mehran; Abzhanov, Arkhat; Herrel, Anthony; Evans, Susan E.; Vickaryous, Matt
ABSTRACT: Osteoderms are mineralised structures consisting mainly of calcium phosphate and collagen. They form directly within the skin, with or without physical contact with the skeleton. Osteoderms, in some form, may be primitive for tetrapods as a whole, and are found in representatives of most major living lineages including turtles, crocodilians, lizards, armadillos, and some frogs, as well as extinct taxa ranging from early tetrapods to dinosaurs. However, their distribution in time and space raises questions about their evolution and homology in individual groups. Among lizards and their relatives, osteoderms may be completely absent; present only on the head or dorsum; or present all over the body in one of several arrangements, including non‐overlapping mineralised clusters, a continuous covering of overlapping plates, or as spicular mineralisations that thicken with age. This diversity makes lizards an excellent focal group in which to study osteoderm structure, function, development and evolution. In the past, the focus of researchers was primarily on the histological structure and/or the gross anatomy of individual osteoderms in a limited sample of taxa. Those studies demonstrated that lizard osteoderms are sometimes two‐layered structures, with a vitreous, avascular layer just below the epidermis and a deeper internal layer with abundant collagen within the deep dermis. However, there is considerable variation on this model, in terms of the arrangement of collagen fibres, presence of extra tissues, and/or a cancellous bone core bordered by cortices. Moreover, there is a lack of consensus on the contribution, if any, of osteoblasts in osteoderm development, despite research describing patterns of resorption and replacement that would suggest both osteoclast and osteoblast involvement. Key to this is information on development, but our understanding of the genetic and skeletogenic processes involved in osteoderm development and patterning remains minimal. The most common proposition for the presence of osteoderms is that they provide a protective armour. However, the large morphological and distributional diversity in lizard osteoderms raises the possibility that they may have other roles such as biomechanical reinforcement in response to ecological or functional constraints. If lizard osteoderms are primarily for defence, whether against predators or conspecifics, then this 'bony armour' might be predicted to have different structural and/or mechanical properties compared to other hard tissues (generally intended for support and locomotion). The cellular and biomineralisation mechanisms by which osteoderms are formed could also be different from those of other hard tissues, as reflected in their material composition and nanostructure. Material properties, especially the combination of malleability and resistance to impact, are of interest to the biomimetics and bioinspired material communities in the development of protective clothing and body armour. Currently, the literature on osteoderms is patchy and is distributed across a wide range of journals. Herein we present a synthesis of current knowledge on lizard osteoderm evolution and distribution, micro‐ and macrostructure, development, and function, with a view to stimulating further work.